Rekonstruksi Perlindungan Anak dalam Hukum Perceraian Islam: Analisis Fath al-Qarib dan Kerangka Hukum Indonesia - Moh Rifqy Mubarrok (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2026)
Divorce in Indonesia has significant repercussions on children’s welfare, yet classical Islamic jurisprudence—particularly the Shafi‘i school—offers a systematic normative framework for post-divorce child protection through the concept of hadhanah (custody). This study aims to analyze the concept of child protection in divorce cases according to the classical text Fath al-Qarib al-Mujib by Shaykh Muhammad bin Qasim al-Ghazi, compare it with Indonesian positive law (Law No. 35/2014 on Child Protection and the Compilation of Islamic Law), and evaluate its alignment with maqashid sharia. Using normative legal research with a library-based case approach, the study employs content analysis, source triangulation, and comparative analysis between classical fiqh and contemporary legal practice. The findings reveal that Fath al-Qarib establishes a structured child protection system based on three pillars: custody (hadhanah) prioritizing the mother (or a specified hierarchy of relatives), maintenance (nafaqah) as the father’s absolute obligation, and visitation rights. However, a systematic implementation gap exists between this normative ideal and Indonesian legal practice, manifested as triadic failure (state, law, and religious institutions). From a maqashid sharia perspective, this gap threatens ḥifẓ al-nafs (protection of life) and ḥifẓ al-nasl (protection of lineage). The research contributes an integrative framework linking classical fiqh, positive law, and maqashid sharia while identifying procedural, institutional, and cultural failures. It recommends strengthening enforcement mechanisms (dwangsom), structured mediation, and shared parenting approaches. Future research should conduct empirical studies on compliance rates and cross-madhhab comparisons.